The influence of water in planning new towns - Tuamsuk, Sommai 1947- (1978)
New town is not an ultimate solution of the rapid urban growth. It is one of the alternative solutions to solve such problems. The main objective of new town development is to promote and maintain such new planned communities in such a state that the well-being of man and the habitat can be perpetuated by utilizing the available natural resources within effective ranges having as a constraint balance of the ecological process. Environment is a complex and interconnected syste, a web and continuum dynamic and ever-changing. Action in one part affects others. Planning should recognize this unity as a primary principle of environment, and realize that environmental planning or planning for environment is a long-range process. Planning needs time to accomplish. It is not a machine that can be manipulated to stop and go whenever the user wants it to. Water is a word that needs no definition. It is natural resource, an environmental element, a source of life of all living things on earth. Before approaching and tackling the existing or foreseen problems of environment in a community, the understanding of the nature of water is a primary necessity in order to understand the total environment. The natural process of ecological build-up begin with water. Community is man. Community is the stage of human existence. In settled communities its environment is shaped by water as this is a vital element of human existence and nature. The assessment of resource, functions, problems and other realted influences of water in relation with man in community, together with past experiences of settlement development will lead to a set of criteria in seeking a habitable new towns.
Vita.
Thesis (Master of Architecture : Community Architecture)--University of the Philippines, Diliman.
Keywords: Town planning; Planned communities; Water and architecture